Interaction between Protein Subunits of the Type IV Secretion System of Bartonella henselae - Shamaei-Tousi, Alireza (American Society for Microbiology, 2004)
In this study we used the yeast two-hybrid system to identify interactions between protein subunits of the virB type IV secretion system of Bartonella henselae. We report interactions between inner membrane and periplasmic proteins, the pilus polypeptide, and the core complex and a novel interaction between VirB3 and VirB5.